Climatologia dos furacões no Atlântico Norte - estudo de caso sobre o Katrina 2005 utilizando modelo simples - Ferreira Neto, José Augusto (Universidade Federal do Rio Grande do Norte, 2023)
This research aimed to quantify and categorize hurricane events that occurred over the North Atlantic Ocean basin from 1961 to 2021, using data from the HURDAT2 database. The goal was to show possible changes in the behavior of these systems by decade, within each hurricane category. A case study was also developed using simulations from an asymmetric hurricane model for Hurricane Katrina in 2005 to verify if the model could accurately simulate this type of system. The applied methodologies, such as cluster analysis, K-means, and the Mann-Kendall test, identified that there is a lower central pressure decay rate for larger hurricanes in categories 3, 4, and 5. The 1960s, 1970s, and 2000s had the highest number of recorded events, all with over 20 events. In 2005, the highest number of events was recorded, with 28 counted between tropical storms and hurricanes. For hurricane trajectories, the largest were observed for hurricanes in categories 3, 4, and 5, and they had the highest presence across continents. It was also identified that the majority of these hurricanes originate from a tropical storm, accounting for over 70% during the study period. Larger hurricanes occurred in a limited number of months when oceanic and atmospheric conditions were favorable. The trend of occurrence has been increasing over the years, along with the number of days with their presence. In regards to simulations, the model was able to satisfactorily reproduce different aspects characteristic of a hurricane of this category. Esta pesquisa teve como objetivo realizar uma quantificação e categorização dos eventos de furacões, ocorridos sobre a bacia do Oceano Atlântico Norte, entre os anos de 1961 até 2021, com informações proveniente do banco de dados do HURDAT2, e com isso mostrar as possíveis alterações ocorridas no comportamento desses sistemas por década, em cada uma das categorias de furacão. Também foi desenvolvido um estudo de caso utilizando as simulações de um modelo simples de furacão, para o Katrina 2005. Com a simulação ...